2017
DOI: 10.1002/ajmg.b.32565
|View full text |Cite
|
Sign up to set email alerts
|

Genetically contextual effects of smoking on genome wide DNA methylation

Abstract: Smoking is the leading cause of death in the United States. It exerts its effects by increasing susceptibility to a variety of complex disorders among those who smoke, and if pregnant, to their unborn children. In prior efforts to understand the epigenetic mechanisms through which this increased vulnerability is conveyed, a number of investigators have conducted genome wide methylation analyses. Unfortunately, secondary to methodological limitations, these studies were unable to examine methylation in gene reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 56 publications
(57 reference statements)
1
31
0
Order By: Relevance
“…Please see Supporting Information Table 1 for a complete listing of the significant markers for each analysis. In addition, to better understand whether the changes at a given locus were related to alcohol or tobacco consumption, the ranking of a given probe with respect to smoking status in the Framingham Heart Study ( n = 1,599) is also provided (Dogan et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Please see Supporting Information Table 1 for a complete listing of the significant markers for each analysis. In addition, to better understand whether the changes at a given locus were related to alcohol or tobacco consumption, the ranking of a given probe with respect to smoking status in the Framingham Heart Study ( n = 1,599) is also provided (Dogan et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although, smoking and drinking are well known to cosegregate (Bierut et al, ) the extent of the comorbidity surprised us with nearly 90% of the first 100 subjects recruited through our current project (R44AA022041) being daily smokers. Given the profound effects of smoking on genome‐wide methylation, (Dogan et al, , ; Zeilinger et al, ) this comorbidity has significant implications on strategies for identifying loci capable of measuring alcohol intake in all potential subjects. In that regard, we note that none of our candidate markers associated with smoking status in any of five genome‐wide methylation datasets in our possession (Dogan et al, , ; Monick et al, ; Philibert, Beach, & Brody, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research is needed to characterize this convergence of genetic effects on growth and placental epigenetic responsiveness to MSDP within similar genomic proximities. It is possible that MSDP, genetic variation, and placental DNAm in these regions yield additive or interactive effects on birth outcomes; prior studies have addressed this question in blood 52,53 . Additionally, while our MSDP-associated CpGs are in similar genomic regions (1 Mb windows) with birth outcome SNPs, very few of our CpGs (9 of 1224) and very few of the birth outcome SNPs (3 of 324) are known placental mQTLs 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…A further possibility for the seemingly conflicting results is interaction with other molecular factors. Recent studies [55,56] have indicated that single-nucleotide polymorphisms influence the smoking-associated CpG sites. These studies further highlight the complexity of molecular networks, and underline the need for functional analysis.…”
Section: Discussionmentioning
confidence: 99%